Metabolic attributes, yield and stability of milk in Jersey cows fed diets containing sodium citrate and sodium bicarbonate - Stumpf, Marcelo Tempel; Fischer, Vivian; Kolling, Giovani Jacob; Zanela, Maira Balbinotti; Ribeiro, Maria Edi Rocha; Abreu, Alexandre Süsenbach de (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to evaluate the inclusion of sodium citrate and sodium bicarbonate in the diet of lactating Jersey cows, and its effects on the metabolic attributes, productivity and stability of milk. We evaluated urinary pH, levels of glucose and urea in blood, body weight, body condition score, milk yield, milk stability (ethanol test), and milk physicochemical properties of 17 cows fed diets containing sodium citrate (100 g per cow per day), sodium bicarbonate (40 g per cow per day) or no additives. Assessments were made at the 28th and 44th days. Supply of sodium citrate or bicarbonate has no influence on the metabolic attributes, productivity, body weight, and body condition score of the cows, neither on the composition and stability of milk.